Recombination-enhanced diffusion of self-interstitial atoms and vacancy-interstitial recombination in diamond - Newton, M; Campbell, B; Twitchen, D; Baker, M; Anthony, T (2002)
In this paper we report the results of EPR and optical studies on vacancies and interstitials produced in type IIa diamond irradiated with 2-MeV electrons at temperatures between 90 and 900 K. Post-irradiation annealing studies at temperatures up to 1900 K were also performed. Data showing recombination-enhanced diffusion of self-interstitial atoms in diamond is presented and our analysis of the phenomena leads us to the conclusion that a highly mobile interstitial I* (possibly a charged/neutral T-d interstitial) is produced by electronic excitation and/or charge transfer. We estimate that the migration energy for I* is 0.3 eV. No evidence for vacancy recombination-enhanced diffusion was observed. The experimental data confirms that there is a significant barrier to vacancy-interstitial recombination in diamond. (C) 2002 Elsevier Science B.V. All rights reserved.